Comparative Study of Mechanical Stresses in Human Limb Bones - Doina Drăgulescu; Lucian Rusu; Vlad Morcovescu; Cris Precup (Applied Bionics and Biomechanics)
This research studies the upper and lower limb bones of elderly persons. The measurements of compressive, tensile and bending forces were performed on 147 specimens: 72 in a compression trial, 21 in a tensile trial and 54 in a bending trial. Bones were extracted from 38 cadavers (60–70-years-old at the time of death). Experimental protocols were developed to minimise the possible errors in obtaining the data. All results were statistically processed. There was a significant difference between the results of both the tensile and bending trials and the compression trial (p = 0.08). Significant differences were observed between the results of the compression test in proximal versus distal ends of the bones (femur, tibia and humerus). After the removal of outlying results, an F-test analysis was performed on all remaining values, establishing different correlation levels between the groups of results. These results were compared with those published by other researchers.